Negative Effects of Long-duration Spaceflight on Paraspinal Muscle Morphology. Issue 12 (15th June 2019) - Burkhart, Katelyn; Allaire, Brett; Bouxsein, Mary L.
Abstract : Study Design: Prospective case series. Objective: Determine the extent of paraspinal muscle cross-sectional area (CSA) and attenuation change after long-duration spaceflight and recovery on Earth. Determine association between in-flight exercise and muscle atrophy. Summary of Background Data: Long-duration spaceflight leads to marked muscle atrophy. However, another negative consequence of disuse is intramuscular fatty infiltration. Notably, few studies have investigated the effects of spaceflight on intramuscular fatty infiltration, or how muscle atrophy is associated with in-flight exercise. Methods: We analyzed computed tomography scans of the lumbar spine (L1/L2) from 17 long-duration astronauts and cosmonauts to determine paraspinal muscle CSA and attenuation. Computed tomography scans were collected preflight, postflight, 1-year postflight, and, in a subset, 2 to 4 years postflight. We measured CSA (mm 2 ) and attenuation (Hounsfield Units) of the erector spinae (ES), multifidus (MF), psoas (PS), and quadratus lumborum (QL) muscles. We used paired t tests to compare muscle morphology at each postflight time point to preflight values and Pearson correlation coefficients to determine the association between muscle changes and in-flight exercise. Results: ES, MF, and QL CSA and attenuation were significantly decreased postflight compared with preflight (−4.6% to −8.4% and −5.9% to −8.8%, respectively, p  < 0.05 for all). CSA of these muscles equaled or exceeded preflight values upon Earth recovery, however QL and PS attenuation remained below preflight values at 2 to 4 years postflight. More resistance exercise was associated with less decline in ES and MF CSA, but greater decline in PS CSA. Increased cycle ergometer exercise was associated with less decline of QL CSA. There were no associations between in-flight exercise and muscle attenuation. Conclusion: Both CSA and attenuation of paraspinal muscles decline after long-duration spaceflight, but while CSA returns to preflight values within 1 year of recovery, PS and QL muscle attenuation remain reduced even 2 to 4 years postflight. Spaceflight-induced changes in paraspinal muscle morphology may contribute to back pain commonly reported in astronauts. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textWe investigated lumbar spine CT images of 17 crewmembers after 4–7 months of long-duration spaceflight. We found an immediate post–flight decline in paraspinal muscle CSA and attenuation. By 1–year post–flight, all muscle parameters returned to pre-flight values except psoas and quadratus lumborum muscle attenuation, which was still reduced 2–4 years post-flight.